Pelatihan dan Pendampingan Pencegahan Perundungan di Sekolah Dasar Laboratorium Percontohan UPI Kampus Serang - Robiansyah, Firman; Salim, Herli; Widjojoko, Widjojoko; Fatihaturosyidah, Fatihaturosyidah; Suprianto, Oki (Jurnal Pengabdian Masyarakat PGSD, 2025)
This Community Service (CS) contained training and mentoring for all teachers and education personnel at the Laboratory Elementary School of UPI Serang Campus. The purpose of this CS is to provide basic knowledge and skills to teachers and education personnel about the prevention and handling of school bullying. The implementation of CS activities is carried out through three main stages. The first stage was an initial survey, aiming to gather information about the demographics of the participants and understand their level of understanding about bullying. This information became the basis for designing training that suited the needs of the participants. The second stage was the training to provide both insights and practical skills that can be applied immediately, which consisted of two main sessions: a session focused on introducing and understanding different forms of bullying, so that participants were able to recognise the signs and effects of this behaviour; and a session provided practical guidance to effectively respond to and deal with bullying in the school environment. The final stage was a final survey to evaluate participants' perceptions of the training materials that had been delivered as well as to formulate a follow-up plan for the workshop in form of lectures, brainstorming and interactive discussions to ensure the sustainability of the programme. The results of the training showed that the education units consisting of teachers and education personnel involved had a better understanding of the concept of bullying. They are expected to follow up on this activity by developing bullying prevention programmes in their respective schools, thus creating a safer and more inclusive learning environment.